Deconstructing public relations : public relations criticism - Mickey, Thomas J. (LEA's communication series., 2003)
This volume provides a critical look at public relations practice, utilizing case studies from public relations, advertising, and marketing to illustrate the deconstruction and analysis of public relations campaigns. Author Thomas J. Mickey uses a cultural studies approach and demonstrates how it can be used as a critical theory for public relations practice, offering real-world examples to support his argument. Through the interpretive act of deconstruction, this book serves to challenge the myth of public relations as an objective ""science,"" allowing the social importance of publi.